2008
DOI: 10.1115/1.2939342
|View full text |Cite
|
Sign up to set email alerts
|

The 12cc Penn State Pulsatile Pediatric Ventricular Assist Device: Fluid Dynamics Associated With Valve Selection

Abstract: The mortality rate for infants awaiting a heart transplant is 40% because of the extremely limited number of donor organs. Ventricular assist devices (VADs), a common bridge-to-transplant solution in adults, are becoming a viable option for pediatric patients. A major obstacle faced by VAD designers is thromboembolism. Previous studies have shown that the interrelated flow characteristics necessary for the prevention of thrombosis in a pulsatile VAD are a strong inlet jet, a late diastolic recirculating flow, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 31 publications
1
52
0
3
Order By: Relevance
“…Previous PVAD studies by Cooper et al 7 and Roszelle et al 18,19 describe the PIV technique used in the study extensively. The images were acquired with a pulse delay of 200 ls and a resolution between 35 and 45 lm/pixel depending on the plane.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous PVAD studies by Cooper et al 7 and Roszelle et al 18,19 describe the PIV technique used in the study extensively. The images were acquired with a pulse delay of 200 ls and a resolution between 35 and 45 lm/pixel depending on the plane.…”
Section: Methodsmentioning
confidence: 98%
“…These include flow characterization, valve selection, valve orientation, device three-dimensionality, and most recently the effect of varying clinical conditions on the flow field. 7,8,15,[18][19][20] Overall, we have found that the PVAD has a flow field with adequate wall washing under normal operating conditions. The reduced volume of the PVAD makes the flow in the body of the pump more sensitive, so that changes in the valve position and inflow and outflow cannulae affect the device flow field.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Previous studies, examining wall location definition, have shown the ability to locate the wall to within a half a pixel and a thorough error analysis was carried out as was detailed in Ref. [21]. From this, the error in the projected vectorto-wall distance is 6 17.5 lm at the low magnification, and 6 6 lm at the high magnification.…”
mentioning
confidence: 99%